Traditional Treatment of Tuju Disease (Rheumatism) in Lontar Usada Based on Bali Local Wisdom - İ Ketut Ardhana; Putu Lakustini Cahyaningrum (Journal of Economy Culture and Society)
Traditional medicine is a nation's culture that needs to be preserved. Globalization has caused some people to use traditional medicine as alternative medicine, especially in the province of Bali, Indonesia, which is familiar with the term usada. This study aims to identify the traditional treatment of tuju (Rheumatic) diseases in lontar usada based on the local Wisdom of Bali. Literature studies were used in the study. Identification was made by analyzing lontar, books, and journals discussing related diseases. The results obtained by traditional medicine have become a cultural heritage reflected in the existence of lontar (Hindu cultural records), which contain types of diseases, medicines from diseases, traditional materials, and procedures for making and presenting traditional medicine. There are thirteen types of diseases and characteristics of diseases in lontar usada. There are four ways traditional health workers acquire their expertise, including Balian Kapican, Balian Katakson, Balian Usada, and Balian Campuran. In traditional medicine practice, rheumatic diseases have three treatment techniques, namely massage (uut), inner energy, and the provision of medicinal herbs. The species of herbs used are Tangerine (Citrus nobilis), Awar-awar (Ficus septica), Jeruju or daruju (Acanthus icifolius L.), Buu Plant, Ginger (Zingiber officinale Roxb), Ki Encok (Plumbago zeylanica L.), Tri Ketuka (kesuna, Jangu, mesui), and Sindrong Jangkep (spices). Usada needs to be preserved as a local culture that can be utilized as a world cultural heritage.